Prevalence of comorbidities in patients with endometriosis of childbearing age in the María Auxiliadora Hospital between 2008-2017 - Infante-Bustamante, Pedro (2018)
Objective: To describe the prevalence of comorbidities in patients with endometriosis of childbearing age in the María Auxiliadora Hospital between 2008-2017.Objective: To describe the prevalence of comorbidities in patients with endometriosis of childbearing age in the María Auxiliadora Hospital between 2008-2017. Methods: A quantitative, observational and descriptive study was carried out. We worked from the database of patients who were diagnosed with endometriosis at the María Auxiliadora Hospital. Results: We found 66 clinical histories that had the definitive diagnosis of endometriosis, of which 60 were of childbearing age, which was divided into 3 age groups, 20 to 40 years with 34 patients and 41 to 50 years with 26 patients. . No patients were found in the group of 11 to 19 years. Comorbidity, in the fertile age group, with the highest prevalence was anemia, with 81.7% (n = 49), followed by pelvic inflammatory disease with 56.7% (n = 34) and myomatosis with 30% (n = 18). ). Infertility was presented in 18.3% (n = 11), obesity 10% (n = 7) and comorbidities with a prevalence lower than 10%, were anxiety with 6.7% (n = 4), depression, arterial hypertension and coronary disease with 5% (n = 3), diarrhea, irritable bowel and constipation occurred in less than 5% of patients and there were no cases of ovarian cancer, myocardial infarction, or lymphoma not Hodking, but in the group of people over 50, who presented 1 case of ovarian cancer. The age group with the highest number of comorbidities was 41 to 50 years with 51.9% (n = 70). Conclusion: We found a large number of cases of comorbidities studied, despite being a small group of patients, being the group of 41 to 50 years the most affected. The high prevalence of anemia in our country may be the reason for the high number in our patients, unlike the pelvic inflammatory disease that has a prevalence similar to that of other studies. DOI 10.25176/RFMH.v18.n4.1731